Uso das mídias sociais como ferramenta de promoção da saúde - Coelho, Amanda Cristina Dias (Universidade Federal do Tocantins, 2022)
In nutrition, health promotion acts under dietary guidelines associated with food quality with the purpose of maintaining health and reducing risks related to poor diet and lifestyle. Digital marketing is a tool that can facilitate the transmission of nutritionist information, strategies and services. This is a descriptive and exploratory research, carried out through an online form, to collect opinions about the possibilities of health promotion in social media. Data were collected between October 20 and 30, 2021. The results showed that WhatsApp is the most popular social media in the state of Tocantins, where most consider the presence of nutritionists relevant in the transmission of nutrition information, and more half of its respondents confirmed the practice of changes stimulated by these professionals in social media. It is concluded that social media can be a digital marketing tool for the transmission of health information, but that the possible benefits of having nutritionists in virtual environments as health promotion strategies is still little discussed.